Trapping hydrogen with a bimetallic interface - Okada, Michio (Animo Repository, 2005)
We report results of a study on the interaction of hydrogen with thin Au films grown on an Ir{111} surface at ≈100 K, using nuclear reaction analysis and first-principles calculations. We found that H atoms can be confined at the interface between the bulk-Ir surface and the Au thin film, which is realized by increasing the binding energy and the activation barrier for desorption via lattice relaxation of the Au layer. ©2005 The American Physical Society.